CELLULAR AND MOLECULAR IMMUNOLOGY OF LUNG CANCER: THERAPEUTIC IMPLICATIONS - Nguyen, Austin Huy (Expert Rev Clin Immunol, 2014)
Though incidence is declining, the prognosis of lung cancer remains poor. This is likely due to lack of early detection and only recent developments in selective cancer therapies. Key immune cells involved in the pathogenesis of lung cancer include CD4(+) T-lymphocytes, macrophages, dendritic cells, and natural killer cells. The growing understanding of these cells indicates a highly complex and intertwined network of their involvement in each stage of lung cancer. Immune cell types and numbers affect prognosis and could offer an opportunity for clinical therapeutic applications. However, an incomplete understanding of immune cell involvement and the underlying processes in lung cancer still remain. More investigation focusing on the role of the immune cells will further the understanding of lung carcinogenesis and develop novel therapeutic approaches for the treatment and management of patients with more specialized and selective lung cancer.